2020
DOI: 10.1093/jpepsy/jsaa097
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Peer Use, Costs and Benefits, Self-Efficacy, and Adolescent E-cigarette Use

Abstract: Objective Prior research identified peer use as a salient risk factor of adolescent electronic cigarette (e-cigarette) use, but has not expanded on the mechanisms of this association. Methods Participants were 562 adolescents recruited from rural and suburban public high schools and an adolescent medicine clinic in the mid-Atlantic United States. Participants completed a packet of questionnaires that assessed demographics, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…As our findings provide further support for the many studies that have found that peer smoking influences teenage e-cigarette use [ 20 , 47 50 ], we suggest that health education interventions that take account of peer influences remain important, particularly as higher levels of peer e-cigarette use [ 51 , 52 ] and favourable e-cigarette peer norms [ 53 ] have been found by other researchers to be related to higher odds of personal e-cigarette use.…”
Section: Discussionsupporting
confidence: 86%
“…As our findings provide further support for the many studies that have found that peer smoking influences teenage e-cigarette use [ 20 , 47 50 ], we suggest that health education interventions that take account of peer influences remain important, particularly as higher levels of peer e-cigarette use [ 51 , 52 ] and favourable e-cigarette peer norms [ 53 ] have been found by other researchers to be related to higher odds of personal e-cigarette use.…”
Section: Discussionsupporting
confidence: 86%
“…Higher prevalence in the school setting could be a function of both response bias because they are in the presence of peers, and/or peer influences that promote use (e.g., peer pressure, increased access to e-cigarettes). Youth e-cigarette use is heavily influenced by the e-cigarette-related perceptions and behavior of their peers [ 25 , 26 , 27 ], and has been increasingly likely to take place in or around school campuses [ 28 , 29 ]. One recent study found that, among sixth-grade students in urban Texas, on-campus learners had greater odds of reporting e-cigarette use susceptibility and ever using e-cigarettes than remote learners [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 , 30 Our study also found that having best friends using e-cigarettes was associated with higher odds of e-cigarette initiation and susceptibility, consistent with what has been reported previously using convenience samples. 31 , 32 According to multiple health theories and models, 44 , 45 , 46 perceived peer approval and use of substances play key roles in influencing early stages of substance use during adolescence. Our findings indicate that these theories and models are also applicable to e-cigarette use.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence about associations of parental and peer use with tobacco use is almost entirely from studies of cigarettes and other tobacco products, 27 , 28 with most of these studies focusing on the associations between adolescents’ cigarette smoking and the smoking status of their friends. 28 , 29 , 30 A few studies have suggested that a similar pattern exists for e-cigarettes 31 , 32 ; however, these studies relied primarily on regional data collected from convenience samples. Nationally representative studies are needed to estimate the associations between parental and peer e-cigarette use and adolescents’ e-cigarette use outcomes.…”
Section: Introductionmentioning
confidence: 99%